Risk factors for mortality in anti-MDA5 antibody-positive dermatomyositis with interstitial lung disease: a systematic review and meta-analysis - Yang, Yahui; Li, Ying; Yuan, Weiwei; Zhang, Shijie; He, Xing; Ji, Jiaqi (Frontiers in Immunology, 2025)
BackgroundAnti-melanoma differentiation-associated gene 5 (MDA5) antibody-positive dermatomyositis with interstitial lung disease (MDA5+ DM-ILD) carries a high mortality risk. This meta-analysis aimed to identify mortality risk factors to guide early clinical intervention.MethodsFollowing PRISMA guidelines, we systematically searched PubMed, Embase, Web of Science, and Scopus for studies published before November 18, 2024. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated for mortality risk factors. Heterogeneity, sensitivity, and publication bias were assessed using Cochran’s Q, one-by-one elimination, and Egger’s tests, respectively.ResultsAmong 1,153 patients from 15 studies, significant risk factors for mortality included older age (HR = 1.04, 95%CI: 1.03, 1.05), smoking (HR = 1.62, 95%CI: 1.06, 2.47), fever (HR = 2.56, 95%CI: 1.66, 3.95), elevated C-reactive protein (CRP) (HR = 1.02, 95%CI: 1.01, 1.02), rapidly progressive ILD (RP-ILD) (HR = 4.02, 95%CI: 1.89, 8.55), high white blood cell count (WBC) (HR = 1.11, 95%CI: 1.02, 1.21), Krebs von den Lungen-6 (KL-6) (HR = 1.11, 95%CI: 1.06, 1.16), ferritin (≥800 ng/mL) (HR = 6.17, 95%CI: 2.51, 15.20), and lymphocyte count (<1.1×109/L) (HR = 4.88, 95%CI: 1.80, 13.20). Higher PaO2 reduced mortality risk (HR = 0.91, 95%CI: 0.86, 0.98). Male, creatine kinase (CK), percent predicted diffusing capacity of the lung carbon monoxide (DLCO%), percent predicted forced vital capacity (FVC%), and erythrocyte sedimentation rate (ESR) showed no significant associations.ConclusionAge, smoking, fever, inflammatory markers, and RP-ILD are critical mortality risk factors in MDA5+ DM-ILD. Early identification and management of these factors may improve prognosis.Systematic review registrationhttp://INPLASY.com, identifier INPLASY202540058.